Avaliação de patentes por abordagens financeiras baseadas em opções reais: estudo de caso de inovações geradas na UFMG - Bruno Rodrigues Faria (2014)
The recognition and correct evaluation of intangible assets based on knowledge gained increasing relevance in the business context, because it is related to its value. Technological innovations among all fields of study contribute to generate relevant competitive advantage. In this context, patents are highlighted to allow legal protection on future benefits. Several academic studies propose to evaluate these types of innovations, but the possibility of an empirical study is still restricted. Withal, Brazil has distinct characteristics in comparison to the main patents generating countries, focusing most of their production in public institutions, especially universities. Therefore, the purpose of this dissertation was to analyze and compare the differences obtained by applying different evaluation methods using case studies that fit this context. This research also allowed to consider the applicability of the methods for an educational institution. The sample consisted of four innovations developed at UFMG and already licensed or with possibility of future licensing. Two cases belong to the pharmaceutical segment and the other two are connected to the field of engineering and physical therapy. The models used allowed comparison between static methods based on cash flows and methods that use real options, considering the flexibility inherent in the licensing process through their contracts. Based on the processes and techniques already in use to evaluate CTIT`s patents, it was applied a single cash flow model standard for all cases. For the option models, it was tested one method of binomial programming, two based on differential equations and two using simulations processes. Initially, the innovations in study had three strategic flexibilities in common, which originate options abandonment of the contract, expansion to international patent and contract extension at the end of the period. Then, the values were estimated by the applying the models and it was found that the theoretical value's underestimation of the static cash flow was observed for all cases. Still, the analysis allowed to determine that the effects of combined options may enhance the future expected earnings and capture more accurately the expected benefits of the asset. About the applicability of these methods, there was a greater difficulty of applying models based on differential equations, which don't improve much to the strategic vision of the managers. The binomial model allows a better visualization of future possibilities, but it is less helpful than the simulation models. These results were also obtained using the Kolmogorov-Smirnov test. To define the type of simulation to be applied, it appears that the development stage of the project is crucial. The problem of data availability, very common to this type of research, was minimized by the major source of industry and specific information that CTIT has. The missing information could be verified with some reliability through interviews with the inventors of each innovation. The variables related to the discount rate showed consistent results with the expected theoretical relation. The sensitivity of the models to interest rate and volatility were, respectively, negative and positive. However, the likelihood of licensing the patent had the greatest impact on value generation, mainly in simulation models. Therefore, the results of this study allows to verify that the application of real options in patents developed in higher education public institutions is viable and generates relevant results.